2022
DOI: 10.1186/s12889-022-12765-1
|View full text |Cite
|
Sign up to set email alerts
|

Global trends in incidence and death of neonatal disorders and its specific causes in 204 countries/territories during 1990–2019

Abstract: Background Neonatal disorders (ND) are a significant global health issue. This article aimed to track the global trends of neonatal disorders in 204 countries/territories from 1990 to 2019. Methods Data was explored from the Global Burden of Disease study 2019. Estimated annual percentage change (EAPC) and age-standardized rate (ASR) were calculated to quantify the trends of neonatal disorders and their specific causes, mainly included neonatal pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“… 3 A study from China reported low NE incidence at 1.5/1000 term live births 48 resembling levels seen in high-income countries with low NMR. 3 61 Low incidence combined with excellent outcomes reported in other studies included in the review is in line with recent Global Burden of Disease data indicating that the burden of NE in China is rapidly decreasing 62 with the rider that assessment bias cannot be ruled out in the register based incidence study.…”
Section: Discussionsupporting
confidence: 78%
“… 3 A study from China reported low NE incidence at 1.5/1000 term live births 48 resembling levels seen in high-income countries with low NMR. 3 61 Low incidence combined with excellent outcomes reported in other studies included in the review is in line with recent Global Burden of Disease data indicating that the burden of NE in China is rapidly decreasing 62 with the rider that assessment bias cannot be ruled out in the register based incidence study.…”
Section: Discussionsupporting
confidence: 78%
“…The Burden of Antibiotic Resistance in Neonates from Developing Societies (BARNARDS) Study conducted an international prospective observational cohort study across 12 clinical sites that highlighted the burden and high mortality of neonatal sepsis among facility-born neonates in low-income and middle-income countries (44). Based on data from the Global Burden of Disease Study 2019, similar results were obtained (45).…”
Section: Not Mentionedmentioning
confidence: 80%
“…A previous study reported that the incident trend of NDs was relatively stable (changes: -0.26%), while the burden of death showed a downward trend (changes: 37.38%) globally from 1990 to 2019 [ 6 ]. China has also made encouraging progress in reducing the burden of NDs over the past three decades in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal disorders (NDs) were a critical part of the SDG, and the disease burden of NDs was comprehensively assessed and quantified by the Global Burden of Disease study (GBD). A previous study reported a plateau and decreasing changing trend in the incidence and mortality of NDs globally from 1990 to 2019, respectively, and it indicated that low and middle socio-demographic index (SDI) settings undertook the heaviest burden [ 6 ]. The population of China represented almost one fifth of the global population.…”
Section: Introductionmentioning
confidence: 99%